(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
The Church "is" communio fidelium and "has" communio hierarchica: foundation and consequences from a canonic constitutional approach ABSTRACT. Ecclesiology has undergone an important development since the Second Vatican Council: it has moved from an institutional ecclesiology to an ecclesiology of communio. Canonical science seeks to adapt to this reality. But in some approaches, communio fidelium and communio hierarchica are still considered on the same plane; in practice, communio fidelium would become a “product” or a “result” of communio hierarchica. But this introduces a “harmful separation between theory and practice” (cf. Veritatis gaudium, n. 4). In this paper I will explain, from a constitutional canonical approach more in line with the ecclesiology of the Second Vatican Council, the foundations and consequences of the instrumentality of the communio hierarchica in relation to the communio fidelium, and what it means that the ‘institutional principle’ is born of the ‘communitarian principle’ (Hervada). SOMMARIO: 1. Planteamiento - 2. Iglesia-Misterio, Iglesia-Comunidad y Iglesia-Sociedad - 3. El protagonismo de la communio hierarchica antes del Concilio Vaticano II - 4. Modos de relacionar la communio fidelium y la communio hierarchica - 5. La Iglesia “es” communio fidelium y “tiene” communio hierarchica - 6. El principio institucional nace del principio comunitario - 7. La autoridad nace de la comunidad - 8. La forma de gobierno eclesial procede de una norma divina positiva - 9. Conclusión: algunas consecuencias canónicas.